From flexibility human resource management to employee engagement and perceived job performance across the lifespan: A multisample study. Issue 1 (26th August 2014) - Bal, P. Matthijs; De Lange, Annet H.
<x xml:space="preserve">Abstract</x> This study investigated the effects of flexibility human resource management (HRM) on employee outcomes over time, as well as the role of age in these relations. Based on work adjustment theory and AMO theory, it was predicted that availability and use of flexibility HRM would be positively related to employee engagement, as well as higher job performance. Moreover, we postulated different hypotheses regarding the role of employee age. While generation theory predicts that younger generations would react more strongly to flexibility HRM in relation to engagement, selection, optimization, and compensation theory of ageing predicts that older workers respond more strongly in relation to job performance. A longitudinal study among US employees and a study among employees in 11 countries across the world showed that engagement mediated the relationships between availability of flexibility HRM and job performance. Moreover, we found partial support for the moderating role of age in the relations of flexibility HRM with the outcomes: Flexibility HRM was important for younger workers to enhance engagement, while for older workers, it enhanced their job performance. The study shows that the effectiveness of flexibility HRM depends upon employee age and the type of outcome involved, and consequently, theory on flexibility at work should take the age of employees into account. Practitioner points Flexibility HRM can be used by organizations to enhance younger workers' engagement, while it can be used for older workers to enhance their job performance. It is important for organizations to not only offer flexibility to their employees, but also to make sure that employees take advantage of these HR practices. Flexibility HRM is important across the world, because it enables people across the world to balance demands from work as well as from private life.